Relationship Of Nurse’s Knowledge About Schizophrenia With The Care Of Schhizoprenia Patients In The Regional General Services Agency Of Aceh Mental Hospital Banda Aceh - Yenikha Gea Arafa (Journal of Midwifery and Nursing, 2022)
Knowledge is needed in every action, including in treating patients, especially schizophrenia. One of the duties of nurses in providing nursing care is to provide health education for patients and families, so good knowledge is needed by nurses to improve the quality of nursing services and achieve optimal health for schizophrenic patients. This descriptive correlation study aims to identify the relationship between nurses' knowledge about schizophrenia and the care of schizophrenic patients in the BLUD. Aceh Mental Hospital using a total sampling method of 85 respondents. Collecting data using questionnaires, namely demographic data questionnaires and knowledge questionnaires about schizophrenia as well as questionnaires for the care of schizophrenic patients. Data analysis using Spearman Rank. The results of data analysis obtained values ??(r = 0.319) and (p = 0.003) with p-value (0.003) < (? = 0.05). This means that Ha is accepted, that is, there is a significant relationship between nurses' knowledge of schizophrenia and the care of schizophrenic patients in the BLUD. Aceh Mental Hospital. It is hoped that nurses will improve the provision of health education and counseling and involve families in patient care, so that the results of patient care and health become more optimal.